(untitled) - Ommen, Tom; Dr. (Andhra Pradesh, India, 2006)
Dr Oommen uses real-life stories, examples, and illustrations to help the reader understand the life-changing strategies of leadership and goal setting... Bringing to life selected Scriptures when illustrating an important leadership or goal-setting principle is an added bonus of this book. Throughout the book, Dr Oommen emphasizes how Jesus handled leadership and goal-setting issues and situations. His examples are scripturally valid
Keywords: Leadership -- Religious aspects -- Christianity